STRATEGI SELF PROMOTION DAN INGRATIATION DI TIKTOK PADA AKUN @CORPORIO TERHADAP MINAT BELI - salma salma; ida jalilah Fitria (Jurnal Ekonomi Bisnis Manajemen Prima, 2026)
This study aims to explore the implementation of self promotion and ingratiation strategies, as well as consumer purchase intention, on the TikTok account @corporio. It also seeks to analyze the influence of these two strategies on purchase intention, both directly and indirectly. A quantitative approach was used through a survey method. Data were collected via a questionnaire distributed to 100 followers of the @corporio TikTok account and analyzed using path analysis with the help of SPSS software. The results show that the self promotion strategy does not have a significant direct influence on purchase intention. In contrast, the ingratiation strategy has a dominant direct effect. Furthermore, self promotion has an indirect effect through ingratiation, indicating greater effectiveness when combined. These findings suggest that combining self promotion and ingratiation can be an effective strategy to build trust and drive purchase decisions on social media, especially TikTok